3D Animation Tutorial Rightway Wearing Syar’ie Hijab - Diniyanti Diniyanti; doni abdul fatah (International Journal of Science, Engineering, and Information Technology, 2016)
Animation is a film that is loved by many children, adults and parents, because animation contains its own uniqueness so that many films are used to meet a general need for communication, both moral messages or a film that is parried from a true story. Learning is an activity of every god creature that is created the most special, that is, human beings who will not cease from second to second since humans are born until humans die, therefore learning is a need for every human being to know things they don't know yet and also to improve oneself. especially for women who have their own demands, especially about covering the genitals, the genitals for women are the whole body, except for the palms and faces, so many women are not concerned with the law and the obligation to cover the genitals, the hijab is very important to cover the genitals, but still many women wear clothes that have a negative impact that will spur sexual harassment. The purpose of making this 3-dimensional hijab syar'ie tutorial video is to make it easier for women to learn how to wear syar'ie without negative impacts, because today many hijabers make modern hijab tutorials and syar'ie forgetting Islamic rules on genitalia just because for the sake of viewers and followers, which will contain comments or have a negative impact on him.